A critical review of heat transfer enhancement methods in the presence of porous media, nanofluids, and microorganisms - Habibishandiz, M.; Saghir, M.Z. (Thermal science and engineering progress, 2022)
•Passive methods do not necessarily increase heat transfer unless they override further pressure drop.•In addition to resolving nanoparticle sedimentation, microorganisms increase heat transfer.•No experimental studies have been done so far regarding microorganisms nanofluid flow in porous media.•Utilization of different microorganisms’ types could be capable of increasing heat transfer. A current common topic of study among scientists and engineers is how to reduce energy usage.As the loading power of engineering devices is constantly upgrading, while they are becoming more and more compacted according to the market demand and in terms of less material consumption, thermal management is getting more complicated. Accordingly, three techniques are proposed to enhance heat transfer including passive, active, and compound (combination of passive and active) methods. Active methods enjoyexternal power sources, while passive methods mostly rely on modification of heat exchange surfaces without the need for any auxiliary tools. In the current paper, an extensive literature review is conducted for three widely used passive techniques including porous media, nanofluids, and microorganisms. Based on studies reviewed here, although hybrid (combination of more than one heat transfer enhancement method) passive methods could accelerate the rate of heat transfer, their productivity depends on whether the heat transfer enhancement acquired compensates the further induced pressure drops or not. Also, although an inconsistency was observed among published articles about the role of microorganisms’ presence in heat transfer intensification of nanofluid flow inside the porous medium, the overwhelming majority of studies proved the contributing role of microorganisms on heat transfer enhancement. There is a great deal of innovative thinking incorporated throughout this review article regarding future studies, and it concludes with key questions for further investigations.